(untitled) (Fiep Bulletin - online, 2014)
The present study aimed to identify and to quantitatively and qualitatively describe the Brazilian south region first state division professional soccer psychologists. Sixteen (16) acting sports psychologists in Paraná, Santa Catarina and Rio Grande do Sul participated, being interviewed about their clubs professional ties, graduation time and opinions on soccer aggressiveness. There were 4 recently graduated, 4 graduated between one and 5 years, one with 5 to 10 years experience, and 7 graduated more than 10 years before the interview. Of the 16, three were university associated, two had ties with the local city halls and 11 were club employees. It was possible to notice that a considerable number of the sports managers is unaware of the psychologist intervention possibilities working with soccer teams. Refering to the small clubs economic limitations, it was possible to notice that university or city hall association may be a viable solution in order to have a sports psychologist on the team.